مذاہب التفسیر الاسلامی کی روشنی میں مستشرق گولڈ زیہرکےاعتراضات کا علمی جائزہ: A Critical analysis of Goldzehr's objections in the light Maẓahib al-Tafsīr al-Islāmī. - Hameed, Abdul; Siddique, Muhammad (Al-Amīr Research Journal for Islamic Studies, 2021)
Goldziher 1850-1921 is a Jewish Orientalist. His interest in the study of Islam took him to the famous Syrian scholar Sheikh Tahir Al-Jazāirī and after spending a long time in his company he moved to Palestine and then to Egypt. Where he benefited from the scholars of Aẓhar University. Among the Orientalists who have formally and fundamentally debated the Qur'anic text and recitations is Gold Poison. He is known for his objections to Hadith and Qur'anic recitations. Dr. Abdul Haleem Al-Najjar, a lecturer at Cairo University, has translated the famous book Muslim Studies of Goldziher into Arabic concerning the different methods and methods of recitation, tafsir, and tafsir of the Holy Quran. This translation was first published by Maktab al-Khanji in Cairo, Egypt in 1955 and reached the hands of the masters of science and literature and became popular. This book is a unique and brand new work of its kind in presenting various topics of the Quran and important aspects of Islamic culture and history in an excellent manner and style. Goldziher proved his meticulous study of the religions of Tafsir al-Islami and his in-depth study of Islam. But there is a difference between a Muslim and a non-Muslim studying Islam, this difference is visible in this book. Goldziher did not describe all the methods of commentary in this book. In addition, the author, like other Orientalists, has erred in interpreting some religious sentiments. Some Muslim scholars call such objections to Goldziher scientific errors. And some see it as part of a deliberate Zionist Orientalist conspiracy. However, the aspects of Tafseer which Goldziher has written about are very important, and much more needs to be written about them. Goldziher's investigation into the Qur'anic text has opened up new avenues for other Orientalists.The said article will present an analytical study of the Qur'anic text, Goldziher's objections to various recitations, and the contents of the book.